2019
DOI: 10.3390/app9050956
|View full text |Cite
|
Sign up to set email alerts
|

In Situ SEM Observation of Structured Si/C Anodes Reactions in an Ionic-Liquid-Based Lithium-Ion Battery

Abstract: In situ scanning electron microscopy (SEM) offers a good way to investigate the structural evolution during lithiation and delithiation processes. In this paper, the dynamical morphological evolution of 3D-line-structured/unstructured Si/C composite electrodes was observed by in situ SEM. The investigation revealed the microstructural origin of large charge capacity for 3D-line-structured anodes. Based on this proposed mechanism, a coarse optimization of 3D-line-structured anodes was proposed. These results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…They concluded that the grid structures were superior to the line structures in terms of isotropic volume expansion and contraction during battery operation. Shi et al [59] used in situ SEM analysis to study the lithiation of laser line structured Si/C anodes in comparison to unstructured ones and proposed an active mass removal of almost 50% for providing enough space to compensate the huge volume expansion.…”
Section: Anodes With Line or Grid Patternmentioning
confidence: 99%
“…They concluded that the grid structures were superior to the line structures in terms of isotropic volume expansion and contraction during battery operation. Shi et al [59] used in situ SEM analysis to study the lithiation of laser line structured Si/C anodes in comparison to unstructured ones and proposed an active mass removal of almost 50% for providing enough space to compensate the huge volume expansion.…”
Section: Anodes With Line or Grid Patternmentioning
confidence: 99%
“…For this purpose, the new electrode architecture, as described and displayed earlier (Figure 2) was developed. In research, silicon-graphite blend electrodes have often been analyzed thus far [2,6,16,[24][25][26]. This work presents new electrode design: a graphite-silicon electrode with separate and vertically aligned areas.…”
Section: Electrochemical Analysesmentioning
confidence: 99%
“…Therefore, in situ/operando techniques were developed to obtain a detailed understanding of the degradation mechanisms of Si-based anodes 36−41 as well as of Si/C anodes. 42 In recent articles, 35,41,43−45 operando measurements have been described as performing the analysis during the charge/discharge procedure, while in situ means the charge/ discharge procedure is suspended and the measurement is carried out at open-circuit potential. We will follow this differentiation in this study, though in the past "in situ" and "operando" haven been often used interchangeably.…”
Section: Introductionmentioning
confidence: 99%
“…Unrepresentative spots due to natural inhomogeneity of the composite electrode structure and artifacts due to sample preparation can cause misinterpretation of these local SEM images and EDX spectra. Therefore, in situ/operando techniques were developed to obtain a detailed understanding of the degradation mechanisms of Si-based anodes as well as of Si/C anodes . In recent articles, ,, operando measurements have been described as performing the analysis during the charge/discharge procedure, while in situ means the charge/discharge procedure is suspended and the measurement is carried out at open-circuit potential.…”
Section: Introductionmentioning
confidence: 99%